2016
DOI: 10.17576/mjas-2016-2003-27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on the Synthesis of Polypyrrole by the Taguchi Method

Abstract: Polypyrrole is a conductive polymer that is widely used in electrochemical applications. To identify the effects of different parameters on the synthesis of polypyrrole, an experimental design based on an orthogonal array L 9 (3 4 ) proposed by Taguchi was applied. The parameters investigated were the oxidant type, molar ratio of oxidant: pyrrole, reaction time and dopant concentration, whereas the response variables observed were the yield, particle size and conductivity. Field Emission Scanning Electron Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Electrical conductivity enables materials to be utilized in electronic devices or as conducting membranes for sensor application 124,125 . The electrical conductivity of PPy is influenced by several crucial factors, such as type of oxidants, initial O/M, dopants or surfactants, polymerization temperature, and polymerization time 126‐128 . Based on the aid of Taguchi method, Utami et al 127 found that the type of oxidants and O/M are the two key factors that significantly affect PPy conductivity.…”
Section: Factors Affecting Ppy Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical conductivity enables materials to be utilized in electronic devices or as conducting membranes for sensor application 124,125 . The electrical conductivity of PPy is influenced by several crucial factors, such as type of oxidants, initial O/M, dopants or surfactants, polymerization temperature, and polymerization time 126‐128 . Based on the aid of Taguchi method, Utami et al 127 found that the type of oxidants and O/M are the two key factors that significantly affect PPy conductivity.…”
Section: Factors Affecting Ppy Conductivitymentioning
confidence: 99%
“…The electrical conductivity of PPy is influenced by several crucial factors, such as type of oxidants, initial O/M, dopants or surfactants, polymerization temperature, and polymerization time 126‐128 . Based on the aid of Taguchi method, Utami et al 127 found that the type of oxidants and O/M are the two key factors that significantly affect PPy conductivity. Moreover, factors such as the type of organic dyes and solvents also have a vital effect on PPy conductivity 129,130 .…”
Section: Factors Affecting Ppy Conductivitymentioning
confidence: 99%
“…An increase in particle diameter with increasing oxidant‐to‐monomer ratio from 1:1 to 2.5:1 was observed. At a low oxidant concentration, NMA monomers are less oxidized into radicals leading to a slower polymerization process and consequently the formation of smaller particles …”
Section: Resultsmentioning
confidence: 99%
“…Finally, the PPy-Chi-BaFe 2 O 4 composite layer was formed on the surface of the gold layer [16]. BaFe 2 O 4 nanoparticles (NPs) were scattered on the surface of layer, and it impressed the morphology of the PPy-Chi-BaFe 2 O 4 nanocomposite layer [31].…”
Section: Preparation Of Sugar Solutionmentioning
confidence: 99%